Modeling of the meso- and submesoscale dynamic processes in the Black sea coastal zones - Olga Dymova (Transactions of the Karelian Research Centre of the Russian Academy of Sciences, 2017)
The article presents an analysis of simulation results for the Black Sea circulation. The calculations were carried out with a horizontal resolution of 1.6~km and taking into account the real atmospheric forcing for 2006 and 2011. Eddies with characteristic mesoscale and submesoscale spatio-temporal parameters were reconstructed in the velocity fields. It is shown that the simulated hydrophysical fields correspond to observed data. The most intensive generation of eddies with the scale of less than 10~km and orbital velocities of 20 -- 30~cm/s was observed in the neighborhood of the Crimean Peninsula, in the north-eastern and south-eastern parts of the sea. Vortex structures in the shelf zones were formed in all seasons with weak winds of directions. Their size depended on the depth and length of the shelf, as well as on the dimensions of coastal capes. The analysis of spatial and temporal variability of salinity fields and the longshore velocity component in the vertical cross-section passing through eddy centers showed that two main mechanisms of coastal eddies formation dominated in the Black Sea. The first mechanism is baroclinic instability, which arises with increasing horizontal density gradient in the periphery of large eddies or currents due to water rising/lowering. The second mechanism is the streamlining of shore inhomogeneities by the coastal current with a velocity higher than 40~cm/s.